Oxford Reading Tree: Level 4: Floppy's Phonics Non-Fiction: How to Pond Dip - Llewellyn, Claire (UK Oxford University Press, 2011)
Floppy's Phonics Non-fiction allow children to practise their decoding and literacy skills in the context of exciting non-fiction books, which include a variety of text types and topics, and support from Biff, Chip, Kipper and Floppy. Books contain inside cover notes to support children in their reading. Help with children's reading development is also available at www.oxfordowl.co.uk. There are 6 Floppy's Phonics Non-fiction titles available at Level 4: A Trip to the Beach: There is lots to do on a trip to the beach. Looking After a Dog: Dogs are good pets. Look at all the things they can do! Find Out! When you need to find out about things, there is a lot to help you. But what's best? Sun and Rain: What is it like in India? Is there sun or rain in Cornwall? Is it hot in Finland? What's for Lunch? Time for lunch! What food is in the lunch boxes? How to Pond Dip: Pond dipping is a lot of fun. This book tells you how to do it.